Molecular insights into LINC complex architecture through the crystal structure of a luminal trimeric coiled-coil domain of SUN1 - Gurusaran, Manickam; Biemans, Jelle J.; Wood, Christopher W.; Davies, Owen R. (Frontiers in Cell and Developmental Biology, 2023)
The LINC complex, consisting of interacting SUN and KASH proteins, mechanically couples nuclear contents to the cytoskeleton. In meiosis, the LINC complex transmits microtubule-generated forces to chromosome ends, driving the rapid chromosome movements that are necessary for synapsis and crossing over. In somatic cells, it defines nuclear shape and positioning, and has a number of specialised roles, including hearing. Here, we report the X-ray crystal structure of a coiled-coiled domain of SUN1's luminal region, providing an architectural foundation for how SUN1 traverses the nuclear lumen, from the inner nuclear membrane to its interaction with KASH proteins at the outer nuclear membrane. In combination with light and X-ray scattering, molecular dynamics and structuredirected modelling, we present a model of SUN1's entire luminal region. This model highlights inherent flexibility between structured domains, and raises the possibility that domain-swap interactions may establish a LINC complex network for the coordinated transmission of cytoskeletal forces.